ANALISIS PENGARUH PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP INCOME SMOOTHING PERUSAHAAN (SUB SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2017-2021) - Nadifa Qatrunnada; Khadijah Nurani (CV. Adiba Aisha Amira, 2023)
This research is a quantitative study that aims to determine the effect of profitability and financial leverage on income smoothing in consumer goods industry sub-sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The number of samples in this study were 30 companies with a sample withdrawal method using purposive sampling. This study uses secondary data obtained through the IDX and company websites. Analysis using multiple linear regression and hypothesis testing using the SPSS 26 application. The results of the hypothesis show that ROA has no effect on income smoothing with a significant value of 0.776 which means> 0.05, it is concluded that ROA has no effect on Income Smoothing. The significant value of ROE is 0.662 which means> 0.05, so it can be concluded that ROE has no effect on income smoothing. The significant value of NPM is 0.856, which means> 0.05, so it can be concluded that NPM has no effect on income smoothing. The significant value of DAR has no effect on income smoothing, this can be seen from the significant value of the variable in the T test which is greater than 0.05, namely 0.709. The significant value of DER has no effect on income smoothing, it can be seen from the significant value of the variable in the T test which is greater than 0.05, namely 0.503. From the test results of the coefficient of determination, obtained (R2) - 0.274 or -27.4%, this means that the independent variable Profitability (ROA, ROE, NPM) and Financial Leverage